Establishing a Core Outcome Measure for Graft Health: A Sandardized Outcomes in Nephrology – Kidney Transplantation (song-tx) Consensus Workshop Report. (July 2018) - Sautenet, Bénédicte; Tong, Allison; Poggio, Emilio; Lentine, Krista L; Oberbauer, Rainer; Mannon, Roslyn; Murphy, Barbara; Padilla, Benita; Chow, Kai Ming; Marson, Lorna; Chadban, Steve; Craig, Jonathan; et al.
Abstract : SONG-Tx . Background: Graft loss, a critically important outcome for transplant recipients, is variably defined and measured and incompletely reported in trials. We convened a consensus workshop on establishing a core outcome measure for graft loss for all trials in kidney transplantation. Methods: Twenty-five kidney transplant recipients/caregivers and 33 health professionals from eight countries participated. Transcripts were analyzed thematically. Results: Five themes were identified. "Graft loss as a continuum" conceptualizesgraft loss as a process, but requiring an endpoint defined as a discrete event. In "defining an event with precision and accuracy, " loss of graft function requiring chronic dialysis(minimum 90 days)provided an objective and practical definition; re-transplant would capture pre-emptive transplantation; relisting was readily measured but would overestimate graft loss; and allograft nephrectomy was redundant in being preceded by dialysis. However, the thresholds for renal replacement therapy varied. Conservative management was regarded as too ambiguous and complexto use routinely. "Distinguishing death-censored graft loss" would ensure clarity and meaningfulness in interpreting results. "Consistent reporting for decision-making" by specifying time points and metrics (i.e. time to event) was suggested. "Ease of ascertainment and data collection" of the outcome from registries could support use of registry data to efficiently extend follow-up of trial participants. Conclusions: A practical and meaningful core outcome measure for graft loss may be defined as chronic dialysis or re-transplant, and distinguished from loss due to death. Consistent reporting of graft loss using standardized metrics and time points may improve the contribution of trials to decision-making in kidney transplantation.